Elements of reflective and non-reflective discourse in an online induction program for experienced and novice science teachers - Farrar, Beth Lauri (Montana State University - Bozeman, College of Education, Health & Human Development, 2009)
Reflection is frequently cited in the literature as integral to the type of learning in which professionals engage. However, throughout the literature the concept of reflection has been ill-defined and shown to be difficult to operationalize in studies. Beginning with a comprehensive review of the literature, this study sought to develop a research based way to operationalize reflection. Once reflection was defined and operationalized, a discourse analysis rubric was designed to identify elements of non reflective and reflective discourse used by participants in an online content-based mentoring and induction professional development program, e-Mentoring for Student Success (eMSS). The rubric was used to conduct a content analysis of online discourse between novice and experienced science teachers participating in the eMSS program. Coders determined which elements of non reflective and reflective discourse, including levels of discourse, were used by different types of participants in the various online discussion areas of the eMSS program. The results of this study showed a higher percentage of novice science teachers' messages were coded as containing overall higher levels of reflective discourse. This difference was partly attributed to the different roles experienced and novice science teachers have in this program. The different eMSS online discussion areas had varying percentages of messages identified as containing different levels of reflective discourse. Different discussion area curriculums, including types of discussion prompts and methods of facilitation, partly attributed to these differences. This study showed the importance of being intentional in the wording or modeling of what is expected from participants as they compose their messages. This study also showed that eliciting reflective thought processes from program participants depends on a variety of factors and can be contextual. No single factor stood out as essential to consistently encouraging reflective thought processes. Recommendations are made for designing program curriculums and facilitating the type of learning that results in the use of reflective thought by program participants.
Keywords: Critical thinking; Reflective learning; Science teachers; Internet